CASHEW TREE TANNINS: A BIO-RENEWABLE SOURCE FOR A NEW GENERATION OF WOOD ADHESIVES: A LITERATURE REVIEW - dos Santos, Carolina Aparecida; Brito, Flávia Maria Silva; Sousa, Thaís Brito; dos Santos, Laise de Jesus; Guimarães Neto, Rosalvo Maciel; Guimarães Junior, José Benedito (Seven Editora, 2026)
Tannins are natural polymers of plant origin distributed in leaves, bark, fruits, and other plant tissues, characterized by their high chemical reactivity. This characteristic is associated with their structure rich in phenolic groups, which gives tannins functional properties relevant for various industrial applications. Among the different plant sources, tannins extracted from the cashew tree (Anacardium occidentale L.) have been gaining prominence as a promising bio-renewable alternative for the development of sustainable materials, especially wood adhesives. Cashew tannins have a high concentration of polyphenols, which favors condensation and crosslinking reactions, essential for the formation of polymeric networks with good mechanical resistance and stability. These properties allow their use as partial or total substitutes for synthetic adhesives based on petroleum derivatives, such as phenolics and urea-formaldehyde, contributing to the reduction of dependence on fossil resources and the emission of toxic compounds. From an environmental and socioeconomic perspective, the use of cashew tannins promotes the valorization of by-products from the cashew supply chain, traditionally exploited mainly for the production of cashew nuts and juice. This approach encourages the integral use of biomass, reduces waste, and generates new opportunities for the development of higher value-added products. Thus, the application of these tannins in ecological adhesives fits within the context of the bioeconomy, aligning technical efficiency, environmental sustainability, and conservation of natural resources, in addition to reinforcing the potential of renewable raw materials in the innovation of materials for the timber industry. DOI: https://doi.org/10.56238/sevened2026.008-095